INVESTIGATION AND OVERVIEW OF SLEEP QUALITY IN MEDICAL RESIDENTS (CIPEEX, 2025)
An individual’s sleep quality directly influences their daily life, positively or negatively altering work performance, learning processes, and the biological homeostasis of the body. In this context, understanding the reality of medical residents is of great importance in measuring how the negative effects of inadequate sleep can develop, affecting both daily functioning and overall quality of life. This study aimed to evaluate sleep quality among residents during hospital shifts, verify the association between residency activities and changes in sleep quality, and identify medical residency programs with higher rates of sleep deprivation and poor sleep quality. This was a cross-sectional, analytical, and comparative study conducted nationwide with 52 medical residents from national programs. The results highlight the need to adapt residency programs to the new demographic reality of the profession, with greater attention to the demands of surgical specialties and first-year residents, given the evidence of deprivation in this group. The study emphasizes the need to improve residents’ sleep and to deepen research on its relationship with decision-making.
Keywords: Sleep quality; Inadequate sleep; sleep disorders